Role of intensive dietary and lifestyle interventions in the treatment of lean nonalcoholic fatty liver disease patients - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Background/aim Although weight loss is recommended for the treatment of nonalcoholic fatty liver disease (NAFLD) in overweight and obese individuals, this treatment modality remains questionable in lean individuals. In this study, we investigated the effects of medical nutrition therapy (MNT) and intensive lifestyle interventions (ILIs) for NAFLD in lean versus obese patients. Methods In total, 35 patients (14 lean and 21 obese) were included in the study. All patients underwent transient elastography examinations, and controlled attenuation parameter (CAP) of >238 dB/m was indicative of hepatic steatosis. After 8 weeks of dietitian follow-up with MNT and ILI, the patients were compared with the baseline. Results Significant weight loss was recorded in both lean (5.4%) and obese patients (5.7%) with NAFLD. The mean BMI decreased from 23.9 (20.5-24.8) to 22.4 (19.5-24.2) kg/m(2)(P = 0.001) in lean patients and from 34.0 (30.0-42.0) to 31.6 (26.9-42.5) kg/m(2)(P < 0.001) in obese patients. The alanine aminotransferase level significantly decreased from 56 (15-163) to 28 (13-98) U/L (P = 0.010) in lean patients and from 27 (13-81) to 22 (13-46) U/L (P = 0.018) in obese patients. The median CAP decreased from 299 (246-360) to 236 (169-318) dB/m (P = 0.002) in lean patients and from 325 (258-400) to 253 (202-383) dB/m (P < 0.001) in obese patients. Moreover, remission of hepatic steatosis was detected in eight lean patients (57.1%) and eight obese patients (38.1%). Conclusion These results indicate that 5% body weight loss in effective in both obese and lean patients resulting in a similar NAFLD remission.
Keywords: clinical nonalcoholic fatty liver disease; nutrition and obesity; nutritional therapy; steatosis; MANAGEMENT; SEVERITY; EXERCISE; OBESITY; ADULTS; NAFLD; RISK; MASS